Effects of two different types of single exercise modes on salivary C-reactive protein concentration, oxidative stress and antioxidant capacity in post-myocardial infarction patients. (1st January 2021) - Gawron-Skarbek, Anna; Chrzczanowicz, Jacek; Nowak, Dariusz; Gawor, Rafał; Kostka, Tomasz
ABSTRACT: Objectives: The aim of the study was to determine the effects of two different types of single cardiac rehabilitation (CR) exercise modes on the inflammation status, oxidative stress and total antioxidant capacity (TAC) of saliva. Methods: The study involved two groups of CR patients: group A ( n = 21) used a cycloergometer, and group B ( n = 21) received breathing and balance exercises. C-reactive protein as an inflammatory biomarker, malondialdehyde (MDA) as a measure of the level of oxidative stress and salivary 2.2-diphenyl-1-picryl-hydrazyl (DPPH) as an index of TAC were performed twice: before the beginning of the CR exercise (pre-CR) and immediately after (post-CR). Results: No significant changes were observed for the inflammatory response of saliva after CR exercise regardless of its type. MDA decreased (pre-CR: 39.7 ± 101.9 vs. post-CR: 16.8 ± 44.3 ng·mL −1 ; p < 0.01) and DPPH increased (pre-CR: 25.9 ± 16.7 vs. post-CR: 32.6 ± 14.0% reduction; p < 0.05) after CR exercise in the group B, with similar but not statistically significant changes in the group A. Discussion: Two popular exercise modes, especially breathing and balance exercises, reduce salivary oxidative stress and enhance the antioxidant potential of saliva in CR patients. The approval of saliva as a non-invasive source of information about inflammation status, oxidative stress and antioxidant capacity in cardiac patients requires further studies.